Phytochemical profiling and identification of chemical markers in four Piper species using liquid chromatography-high resolution mass spectrometry for authentication of herbal products - Hartanto Nugroho, Laurentius; Utaminingsih; Sri Hartini, Yustina; Julianus, Jeffry; Susandarini, Ratna (Agriculture and Natural Resources, 2026)
Importance of the work: Often, medicinal and pharmacological properties are determined based on phytochemical contents, emphasizing the need for phytochemical profiling of Piper spp. Objectives: To analyze the phytochemical profiles of Piper crocatum, Piper aduncum, Piper betle and Piper retrofractum and to identify chemical markers specific to each species. Materials and Methods: Leaves of the four Piper species were extracted using maceration, with three replications for each species. Each extract was analyzed using ultra high-performance liquid chromatography linear trap quadrupole-Orbitrap mass spectrometry and the MetaboAnalyst 6.0 software. Principal component analysis was used to determine sample groupings and similarities and differences of the compounds from the four Piper species. Results: Each species had a specific phytochemical profile composed of different secondary metabolite compounds. There were substantial variations between the components of compounds of mature and old leaves. The qualitative and quantitative analysis of 83 secondary metabolite compounds successfully identified the presence of chemical markers in each species. Main finding: The liquid chromatography-high resolution mass spectrometry method and multivariate data analysis showed potential to produce phytochemical profiles and to identify chemical markers in different Piper spp. for application in the development of modern drugs requiring authentication of the medicinal plant source.